PERSPEKTIF GENDER DALAM LITERASI MEMBACA: INTERSEKSIONALITAS BUDAYA PADA ANAK DAN REMAJA DI WILAYAH MARJINAL 3T INDONESIA: PERSPEKTIF GENDER DALAM LITERASI MEMBACA: INTERSEKSIONALITAS BUDAYA PADA ANAK DAN REMAJA DI WILAYAH MARJINAL 3T INDONESIA - Fatin, Yustina Mince (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2026)
The widespread assumption that girls consistently outperform boys in reading literacy does not hold uniformly across educational levels, particularly in Indonesia's Frontier, Outermost, and Disadvantaged (3T) regions. This anomalous pattern only becomes visible once the data are disaggregated by educational level and region. This study employs a scoping review of 25 scientific articles and non-governmental institutional reports, following the PRISMA-ScR protocol and a three-stage thematic analysis comprising descriptive trend mapping, moderator interaction analysis, and evidence quality appraisal. The review finds that girls' consistent literacy advantage at the early childhood through lower primary level reverses once students reach junior secondary school, where boys with a strong growth mindset demonstrate more competitive achievement. Data from INOVASI (n = 18,370 students across 8 provinces) and mother-tongue-based studies (n = 168–4,111 students) show that gender, mother tongue, and geographic location mutually reinforce one another's negative effects, producing a far more complex pattern of vulnerability than national surveys where biased toward urban samples would suggest. Mother-tongue instruction can function as either an equalizer or a multiplier of vulnerability, depending on how it is taught, while the effectiveness of growth mindset interventions is strongly contingent on the readiness of basic infrastructure. The study concludes that gender-inclusive literacy interventions in 3T regions must be sequenced, beginning with the improvement of basic infrastructure, followed by the integration of mother tongue as a pedagogical bridge, sustained teacher capacity-building, the deconstruction of domestic gender roles, and greater flexibility in academic calendars. The study further underscores the need for gender-disaggregated longitudinal research in 3T regions, which remain significantly under-researched.